Comentario de libro - Merahed, Andrea Fabiana; García, Marisol (Cuaderno Urbano, 1995)
Harvey, David. The Condition of Postmodemity. An Enquiry into tbe Origins of Cultural Cbange. Massachusetts. USA. Blackwell lnc. 1991.